South Sudan: Elites, Ethnicity, Endless Wars and the Stunted State - Nyaba, Peter Adwok (Book collections on Project MUSE., 2019)
The elites -- whether political, military, or economic -- constitute a determinant force in state formation and the nation-building project in post-colonial transitions. The absence of a scientific understanding of the socioeconomic and political configuration of South Sudan has obfuscated the liberation struggle and generated ethnic nationalism and the emergence of a parasitic class that is completely alienated from the masses of the people. South Sudan, the highly hyped youngest state in Africa and the world, is in a deep social, economic, and political crisis characterised by a low-intensity civil war, immense suffering and material deprivation of the people. It has internally displaced hundreds of thousands of people who live in "protection of civilian" sites in major towns under the care of United Nations Mission in South Sudan. Three and a half million have crossed international borders to seek refuge in Uganda, the Democratic Republic of the Congo, Sudan, Ethiopia, and Kenya. The ruling elite, completely unperturbed by the deep humanitarian crisis and apparent near collapse of the state, clamour for power sharing. Together with foreign collaborators, they have enriched themselves and fuelled the war through the extraction and plunder of the country's natural resources. This book is a critical analysis of the socioeconomic and political failures of South Sudan's leaders who have plunged the nascent state into the abyss. South Sudan: Elites, Ethnicity, Endless Wars and the Stunted State is likely to achieve its objective of stimulating debate about the future of South Sudan as a viable polity. The hope is that readers, through the debate generated by this book, will rediscover the commonality that marked the struggle for freedom, justice, and fraternity, and abandon ethnic ideologies as a means of constructing a modern state in South Sudan. South Sudan: Elites, Ethnicity, Endless Wars and the Stunted State is a must-read for South Sudanese intellectuals who want to reshape the socioeconomic and political development trajectory.